Multi-Omics Analysis for Transcriptional Regulation of Immune-Related Targets Using Epigenetic Data: A New Research Direction - Huang, Chenshen; Zhang, Na; Xiong, Hao; Wang, Ning; Chen, Zhizhong; Ni, Zhizhan; Liu, Xiaohong; Lin, Boxu; Ge, Bujun; Du, Bing; Huang, Qi (Frontiers in Immunology, 2022)
Background: Currently, a comprehensive method for exploration of transcriptional regulation has not been well established. We explored a novel pipeline to analyze transcriptional regulation using co-analysis of transcriptome data (RNA-seq) and epigenetic data (ATAC-seq, ChIP-seq). Methods: The GPCRs possibly associated with macrophages were further filtered using a reduced-Cox regression model. ATAC-seq profiles were used to map the chromatin accessibility of the GPRC5B promoter region. Pearson analysis was performed to identify the transcription factor (TF) whose expression was correlated with open chromatin regions of GPRC5B promoter. ChIP-seq profiles were obtained to confirm the physical binding of GATA4 and its predicted binding regions. For verification, quantitative polymerase chain reaction (qPCR) and multidimensional database validations were performed. Results: The reduced-Cox regression model revealed the prognostic value of GPRC5B. A novel pipeline for TF exploration was proposed. With our novel pipeline, we first identified chr16:19884686-19885185 as a reproducible open chromatin region in the GPRC5B promoter. Thereafter, we confirmed the correlation between GATA4 expression and the accessibility of this region, confirmed its physical binding, and proved in vitro how its overexpression could regulate GPRC5B. GPRC5B was significantly downregulated in COAD as seen in 28 patient samples. The correlation between GPRC5B and macrophages in COAD was validated using multiple databases. Conclusion: GPRC5B, correlated with macrophages, was a key GPCR affecting COAD prognosis. Further, with our novel pipeline, TF GATA4 was identified as a direct upstream of GPRC5B. This study proposed a novel pipeline for TF exploration and provided a theoretical basis for COAD therapy.